Caesarean Scar Pregnancy: Single Dose of Intrasac Ultrasound-Guided Methotrexate Injection Seems to be a Safe Option for Treatment - Rouvalis, Angeliki; Vlastarakos, Panagiotis; Daskalakis, Georgios; Pouliakis, Abraham; Stavrou, Sofoklis; Tsiriva, Maria; Giourga, Maria; Gerede, Angeliki; Pappa, Kalliopi; Gregoriadis, Themos; Vlachos, Dimitrios-Efthymios; Rodolakis, Alexandros; Domali, Ekaterini (Ultrasound International Open, 2023)
The purpose of the study was to assess the efficacy of local ultrasound-guided methotrexate injection in patients with caesarean section scar pregnancy, to chart the course of beta-human chorionic gonadotropin levels (HCG) after treatment, and to see if HCG levels are correlated with clinical presentation.Between May 2018 and January 2021, data were collected retrospectively from the Early Pregnancy Unit of a tertiary hospital.Our clinic assessed 20 patients; one disputed terminating the pregnancy and was not included in the research. The remaining 19 patients, with a median age of 34 years, received intragestational sac methotrexate injection under ultrasound guidance. 7w3d was the median gestational age. These women had one to four previous caesarean sections, with a mean of 1.60±9. Patients with caesarean scar pregnancy most typically presented with spotting (42.1%), whereas 26.3% were asymptomatic. Except in cases of pain, the symptomatic women’s HCG levels were lower than in the non-symptomatic women. The level of HCG in patients with pain was approximately double that of non-pain patients (p=0.2557). In our series, intragestational sac methotrexate injection was effective in 17/19 women, or 89.5% (95%CI: 75.7-100%). HCG levels were undetectable in 97.6±30 days on average (minimum: 42 days, maximum: 147 days).Caesarean scar pregnancy is a rare possibly fatal condition with no consensus on the optimal treatment. An experienced Early Pregnancy Unit member performing local methotrexate injections under ultrasound guidance is a feasible and successful strategy in clinically stable patients.
Keywords: ectopic pregnancy; cesarean scar pregnancy; transvaginal ultrasound; methotrexate; gynecology